Fine mapping and multidimensional analysis of carbon emission reduction in China - Xu, Feng; Zheng, Xinqi; Zheng, Minrui; Liu, Dongya; Ma, Yin; Wang, Tingting; Han, Xu (Frontiers in Ecology and Evolution, 2023)
With the continuous intensification of global climate change, carbon peaking and carbon neutrality have become hot topics of common concern among countries around the world. How to accurately measure the carbon emissions between regions and cities and towns so as to formulate differentiated reduction and carbon neutrality policies has become a challenging problem. To this end, we drew a 250 m resolution grid map of carbon emission data and constructed a national-level (2800 county-level units) database for China's carbon emissions. We analyzed it from multiple perspectives such as overall characteristics, urban agglomerations, county-level units, population density, per capita disposable income, etc., providing new ideas for studying the spatial pattern dynamics of multi-scale footprints. The results show that (1) The 250m resolution Carbon Emission Database drawn in this study includes national level, provincial level , county level , urban rural areas etc., which can realize the dynamic research on multi-scale footprint spatial pattern; (2) The top 5% area with highest Carbon Emissions accounts for about 1/5 of total Carbon Emissions in China，and about 1/4 areas account for more than 50% of total Carbon Emissions;(3)The potentials for reducing carbon emissions in China's rural areas are underestimated by more than 10%, while those in western regions are growing rapidly due to poverty alleviation; (4) An inverted U type "environmental Kuznets curve" is formed between disposable income and emissions intensity，and different regions have different consumption patterns. This study provides a new approach for formulating reduction policies at different levels across the country.